Unite against the war - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Silk screen print of two hands in opposing sections within a yin and yang symbol. One hand is in a clenched fist and the other hand showing the peace sign (index and middle finger in V shape). The words "UNITE" appear on top of the symbol and "AGAINST THE WAR" are written on the bottom of the symbol.